The fifth main-sequence magnetic B-type star showing coherent radio emission: Is this really a rare phenomenon?. (5th September 2019) - Das, Barnali; Chandra, Poonam; Shultz, Matt E; Wade, Gregg A
ABSTRACT: We report the discovery of intense, highly directional radio emission from the Bp star HD 35298, which we interpret as the consequence of Electron Cyclotron Maser Emission (ECME). The star was observed with the Giant Metrewave Radio Telescope near the rotational phases of both magnetic nulls in band 4 (550–750 MHz) and one of the nulls in band 5 (1060–1460 MHz). In band 4, we observed flux density enhancement in both circular polarizations near both magnetic nulls. The sequences of arrival of the left and right circularly polarized pulses are opposite near the two nulls. In band 5, we did not have circular polarization information and hence measured only the total intensity light curve, which also shows enhancement around the magnetic null. The observed sequence of the circular polarization signs in band 4, compared with the longitudinal magnetic field curve, is able to locate the hemisphere from which ECME arises. This observational evidence supports the scenario of ECME in the ordinary mode, arising in a magnetosphere shaped like an oblique dipole. HD 35298 is the most slowly rotating and most distant main-sequence magnetic star from which ECME has been observed.